Use of Interdiscipline Integration in the Teaching of Physics (Journal of Pedagogical Inventions and Practices, 2022)
The article discusses the discipline "physics", which is studied in medical universities. The analysis of the content of this discipline is carried out. Highlighted professionally oriented questions disclosed in the discipline "physics". A classification of professionally oriented issues is given. The article describes professionally oriented physical tasks that can be used in the process of studying physics in medical universities.